Science Centres as The Drivers of Change on Social and Educational Arena - Gotwald-Feja, Beata; Beata, Gotwald-Feja; Marlena, Kowalczyk (International Journal of Economics, Business, and Entrepreneurship, 2018)
Current situation at the educational market is extremely dynamic. It can be analyzed from a perspective of a changing environment, including new profiles of sellers and product competition, and the customers’ requirements being influenced by technological, social and psychological circumstances. The general aim of the article is to present science centres as the drivers of change in contemporary reality. In the first part, the general features of contemporary customers shall be presented, starting with their attitude towards the sellers and the offer itself.